Porous frameworks from nanoclays, assisted by bio-templates from Moringa Oleifera - Calle Luzuriaga, María Emilia (2022)
This undergraduate project belongs to a multidisciplinary INEDITA project that involves the School of Chemical Science and Engineering, School of Earth Sciences, Energy and Environment, and School of Physical Sciences and Nanotechnology. The main objective of this research is to provide a literature review on several topics as a foundation that leads to the proposal of a synthetic route of a zeolitic porous framework from Ecuadorian Clays, in a nanoscale (nanoclays), assisted by the implementation of a bio-template obtained from Moringa Oleifera extracts, using both a hydrothermal and a sol-gel method approach. This thesis research will be conducted considering the evaluation of clay samples collected in Ecuador that are characterized via XRD, which is briefly discussed in the theoretical part of this document. The proposal of the synthetic route will provide a detailed process to follow, as well as a detailed characterization description for the resulting products.